Henneguya cynoscioni sp. n. (Myxosporea: Bivalvulida), an agent of severe cardiac lesions in the spotted seatrout, Cynoscion nebulosus (Teleostei: Sciaenidae) - Dyková, Iva; Buron, Isaure de; Roumillat, William A; Fiala, Ivan (Folia parasitologica, 2011)
A new myxosporean species, Henneguya cynoscioni sp. n., is described from the spotted seatrout, Cynoscion nebulosus (Cuvier) (Sciaenidae) as a causative agent of cardiac henneguyosis. This new myxosporean species is characterized by the morphology of spores and the sequence of SSU rDNA. Examination of 227 spotted seatrout from four South Carolina estuaries in 2008-2010 revealed a 33.5% total prevalence of H. cynoscioni. Henneguya cynoscioni produces lesions in the bulbus arteriosus, its specific site of infection. The severity of lesions and their impact on the bulbus arteriosus is proportional to the number of plasmodial stages developing in this segment of the heart, being most pronounced in host reaction directed against spores liberated from plasmodia.
Keywords: financování organizované; ryby; Financing, Organized; protozoální infekce zvířat; nemoci ryb; Phylogeny; Fish Diseases; Fishes; fylogeneze; spory protozoální; Protozoan Infections, Animal; Heart Diseases; Myxozoa; Spores, Protozoan; nemoci srdce